2020
DOI: 10.1002/jmv.26185
|View full text |Cite
|
Sign up to set email alerts
|

Viral load of respiratory syncytial virus among children from primary care and hospital settings admitted to a university hospital in Brazil (2009‐2013)

Abstract: Respiratory syncytial virus (RSV) is a relevant cause of acute respiratory infection among children. Viral replication and immune conditions may account for severity. RSV viral load (VL) was assessed in 486 children (290 hospitalized and 196 from primary care) attended at São Paulo Hospital from 2009 to 2013. VL was calculated by real‐time reverse transcription‐polymerase chain reaction and expressed in Log10 RNA copies/mL. Coinfection with rhinovirus (RV) and influenza A virus was also tested. Young children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…However, differences between viruses may be plausible in light of the discrepant baseline demographics such as age and diagnosis, with FLU patients being substantially older and presenting with FWS more frequently than RSV patients. Similarly, we did not investigate viral codetections, for which conflicting results had been reported, [29][30][31][32] partly explained by competitive interplays between different viruses such as RSV and HRV. 33 In addition, our cohort consists of non-ICU patients, which limits the inference regarding very severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, differences between viruses may be plausible in light of the discrepant baseline demographics such as age and diagnosis, with FLU patients being substantially older and presenting with FWS more frequently than RSV patients. Similarly, we did not investigate viral codetections, for which conflicting results had been reported, [29][30][31][32] partly explained by competitive interplays between different viruses such as RSV and HRV. 33 In addition, our cohort consists of non-ICU patients, which limits the inference regarding very severe cases.…”
Section: Discussionmentioning
confidence: 99%
“…The quantum of direct cytopathic effects exerted by RSV on respiratory epithelium might depend on the viral load (4), however, it is still under speculation because of contradictory findings (5)(6)(7). The Th1 cytokines are needed for viral clearance but an overwhelming secretion of pro-inflammatory cytokines like IL-6 and TNFα cause recruitment of neutrophils that damage the respiratory epithelium (8).…”
Section: Text Introductionmentioning
confidence: 99%
“…Positive correlation of TNFα & IL-10 (r = 0.464, p <0.001), TNFα & IL-6 (r= 0.360, p <0.001), TNFα & MMP-9 (r =0.208, p <0.05) and IL-10 & IL-6 (r = 0.468 p <0.001) cytokines and inverse correlation of MMP-9 & IFN-Ƴ (r = -0.352, p <0.01) was observed with severe ALRTI patients.DiscussionAn early recognition of disease progression, based on specific biomarkers rather than subjective scoring systems, is imperative to decrease the morbidity and mortality associated with RSV. The association of viral load with disease severity remained controversial (25-27).Haddadin et al 2020(5) and Cruz et al 2020(6) have reported a positive correlation with disease severity whereas Vianna et al 2021(7) documented that viral load had no relation with severity of disease. Our data suggested that viral load does not have any significant variation with the age or requirement for intensive care management, however, it was a marker for transition from non-severe to severe ALRTI.…”
mentioning
confidence: 99%
“…Nos países em desenvolvimento as doenças agudas do trato respiratório inferior constituem importante causa de internação hospitalar de crianças com idade inferior a cinco anos (Gralinski & Baric, 2015). Na maioria das vezes, tem como etiologia viral como por exemplo o vírus respiratório sincicial, seguido do parainfluenza, influenza e adenovírus (Cruz, de Souza Luna, Alves, Conte, & Bellei, 2021;Zhu et al, 2021).…”
Section: Introductionunclassified